Permeability and removal rate of compacted clays to organic and inorganic matters - Ozcoban, M. S. (NATL INST SCIENCE COMMUNICATION, 2008)
Compacted clays are widely used for lining solid waste landfills containing wide range of organic and inorganic compounds which cause a major threat to groundwater quality. This study analyses change in permeability of compacted clays due to chemical reactions between clay and permeant. In first stage, permeability of compacted clay (uncontaminated and contaminated) samples was investigated by scanning electron microscope. In second stage, influent and effluent analyses was performed in order to determine treatment capability of compacted clay.
Keywords: chemical oxygen demand (COD); compacted clay; inorganic matter; organic matter; permeability; Total Kjeldahl Nitrogen (TKN); Engineering